Post-graduation in nursing in Brazil: analysis of dissertations and thesis about arterial hypertension and diabetes mellitus between 1972 and 2004 - Abreu, Rita Neuma Dantas Cavalcante de; Moreira, Thereza Maria Magalhães (Rev Rene, 2007)
The objective of this research was to investigate the knowledge produced in the Brazilian Post graduation courses in Nursing about hypertension and diabetes from 1972 to 2004. The bibliographical study related abstracts of dissertations and thesis from the Center of Studies and Researches in Nursing (CEPEn). They identified 109 researches, 71 of which were from Universities in São Paulo, like Ribeirão Preto School, and others from the Federal University of Ceará as wel as from the Federal University of Santa Catarina. Most of the data collected were from the master degrees courses, (79.8%), with great distinction for the period between 1996 and 2004 with 84 studies. The majority, (44.9%) of the researches was of the quantitative kind and many did not have theory as a referential (57.8%). The studies about hypertension were concerned, mainly, with verification of the blood pressure and adhesion to the treatment. As for the diabetes most of the researches were about education in health and nursing care in the illness. The results showed up development in the scientific production investigated. It is recommended to invest in the development of dissertations and thesis in the area, especially in regions with low scientific production.